A Mismatch in Future Narratives? A Comparative Analysis Between Energy Futures in Policy and of Citizens - Haarbosch, Simone W.; Kaufmann, Maria; Veenman, Sietske (Frontiers in Sustainable Cities, 2021)
In the Netherlands, one of the goals of the energy transition is to expand the energy neutrality of houses up to 1,5 million houses until 2030. Citizens are expected to play an important role in this process, but the implementation is hampering, as citizens do not take up the responsibility the policy requires. Policy documents tend to anticipate futures changes from an economic rationale, which tends to align more clearly with the anticipated futures of higher educated, financially wealthy households. So, in a broader perspective, it is unclear how the future desires and expectations of citizens are represented in policy. Often, policies focus on the implementation of best-practices, in contrast, this study investigated in the potential mismatches between futures of citizens and environmental policies. As (policy) narratives of the future are performative, excluding certain stakeholders’ perceptions might lead to energy injustice and could jeopardize the implementation of the energy transition. Indeed, expectations and desires of citizens seem not to be considered as they are based on different rationales (e.g. clean, green, safe living environment). This paper aims to analyse the future “narrative mismatches” (Ottinger, 2017) in the context of the energy transition in the Netherlands. Therefore we combine a futures perspective, which distinguishes between expected, desired and strategic future; and an energy justice perspective as we want to analyse how different issues of energy justice are recognised in these future narratives. Our research question is ‘How do policy future narratives on energy relate to future narratives that are important to citizens’ everyday life in the Netherlands?’ A narrative approach had been chosen to conduct a comparative analysis between a set of policy documents and the narratives of 30 local citizens. We identified several future narrative mismatches, which can be distinguished in two main types: (1) opposing mismatches, where policy narratives and narratives of citizens anticipate antagonistic futures, and (2) disconnected mismatches, where the mismatch emerges because narratives do not engage with each other and focus on different issues.